FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM PEMBELIAN BUAH JERUK LOKAL DAN BUAH JERUK IMPOR DI KOTA MALANG (Studi Kasus di Hypermart Malang Town Square) - Pudjiastuti, Agnes Quartina; Priyambodo, Ayu Wulandari; Pebrianto, Petrus (Agridevina : Berkala Ilmiah Agribisnis, 2023)
Consumer decisions in purchasing local and imported citrus fruits as a decision-making based on the receipt of information obtained. The research was conducted at the Hypermart Malang Town Square Malang City in July-August 2022 using a quantitative descriptive method. Data collection techniques are observation and interviews. The number of samples is 100 people. Data analysis included validity, reliability, classical assumptions, multiple linear regression, F test and t test  as well as the fishbein multiattribute test which were performed statistically using the Statistical Product and Service Solution version 23.64 bit. The results showed that consumer decisions in buying local citrus fruits amounted to 12.98 categorized in the Neutral interval scale range, with a level of confidence and level of evaluation (importance) obtained results (bi) of 3.63 these results belong to the category of level of confidence namely Agree and results ( ei) of 3.54 these results belong to the category of importance level is Important. Consumer decisions in purchasing imported citrus fruits are 13.46 categorized in the Neutral interval scale range, with the level of confidence and the level of evaluation (importance) the result (bi) is 3.63. The results fall into the category of the level of confidence that is Agree and the result (ei) of 3.67 these results belong to the category of importance level is Important. And the factors that influence consumer decisions in buying local oranges are the price of local oranges and income. The factor that influences consumer decisions in purchasing imported citrus fruits at Hypermart MATOS is price. Keywords: purchasing decisions, local oranges, imported oranges.   DOI : https://doi.org/10.33005/agridevina.v12i1.3893